Pathways to mental health care during the COVID-19 pandemic: a study from rural tertiary government mental health facilities in India - Jithin Jaise; Kannappa V. Shetty; Sanjeev Kumar Manikappa; Urmila Bamney (MGM Journal of Medical Sciences)
Background: Understanding the routes individuals take to access mental health care facilities for treatment is crucial for developing effective treatment strategies and policies for those grappling with mental illness. These routes are commonly referred to as pathways to mental health services. Materials and Methods: A descriptive research design was utilized, alongside simple random sampling, to select a sample of 30 participants. Along with gathering sociodemographic variables, data collection involved utilizing the World Health Organization Pathways to Care Performance tool at rural government hospitals in India. Results: The results of the research show that 50% of the population initially sought assistance from psychiatric services, whereas 43.3% consulted native or religious healers for mental illness treatment. It is worth noting that the majority of urban participants primarily utilized psychiatric services. Furthermore, the study highlights that delays in treatment are more common among patients who initially sought help from religious or native healers, especially those from rural backgrounds. Conclusion: This study indicates that treatment delays are more significant among the rural population during the COVID-19 pandemic.